Kopyo'an Marriage(Education Of Students' Ketaawadhu’an At The Boarding School Al-Urwatul Wutsqo Islamic Boarding School, Jombang) - Qurrotul Ainiyah; Ali Mustofa (Institut Attanwir Bojonegoro, 2025)
Tawadhu' or 'humility' is an attitude that cannot arise by itself, because tawadhu' must bring his heart to submit, be obedient, surrender to Allah, and have compassion for humans. There are four aspects of attitude in compiling the tawadhu scale, namely showing respect and gentleness, communicating in a polite manner, apologizing if you act, and praying. If a person carries out these four aspects seriously, he will achieve an attitude of humility in him. One form of tawadhu' of a santri to Kyai is shown by the students of the Pondok Pesantren Al-urwatul Wutsqo Jombang in the way of marriage. The guardians or the parents of the students send their children to the Kyai to choose and determine their child's mate (partner). Guardians and students learn to accept God's destiny through obedience to the kyai to be matched and finally married to whoever is chosen and determined by the kyai by the process of matchmaking, ta'aruf or even by kopyo'an (lottery).